Caddisfly larvae visual system: reponse to light - Grinager, Jeff. (My University, 2009)
Understanding the behavior the caddisfly larvae (Trichoptera, Integripalpia) can have implications in a variety of areas (i.e. the fishing industry) and issues surrounding environmental impacts. This study examines the caddisfly larvae's response to a controlled light stimulus. Experiments were completed in an environment designed to mimic the larvae's natural habitat while controlling the light exposure. During experiments, the majority of the animal's tank was kept completely dark with the exception of a narrow, defined light path which resulted in three different levels of light exposure within the tank. The caddisfly larvae's location and head orientation with respect to the three light levels were recorded. These experiments suggest that caddisfly larvae migrate to lighted areas and not towards darkness. Additionally, head orientation tends to be towards the lighted areas in the tank, similar to nonaquatic insects, but not overwhelmingly toward the source of the light. Furthermore, once in a lighted condition,either direct or ambient light, caddisfly larvae tend to stop moving and remain in the lighted condition.
Keywords: Insects--Effect of light on; Caddisflies--Larvae.